KARAKTERISTIK CO2 PERMUKAAN DI BANDUNG TAHUN 2008-2009 (PENGUKURAN TETAP DI WILAYAH PASTEUR) - Chunaeni Latief,; Asif Awaludin; Afif Budiyono (Jurnal Sains Dirgantara, 2010)
A fixed instrument for CO2 measurement (LPN SATKLIM-1B) has been built and installed at LAPAN Bandung, started by using a direct recorder system on the computer then it is completed with data connection to the CO2 monitoring web server. The CO2 sensor used by NDIR technology has been corrected by the temperature and pressure compensation. The sensor was installed on 15 m above ground level, acquired and also recorded its data by monitoring the software developed by using the Microsoft Visual Basic 6.0. From the recording result of measurement data in Bandung from 2008 until 2009, with one minute interval data, it was obtained that the data characteristic compared to the measurement data from Global Atmospheric Watch (GAW) station in Kototabang (using spectroscopy technology) and Mauna Loa, all of them have the same pattern. From one year analysis (2008 – 2009) it was also obtained that by the increase of motor vehicle in Bndung for about 226,500 vehicle a year, 76% land building, and just 8.7% green open spaces, the CO2 has increased 1.5 ppm and the temperature from AWS data 2008-2009 (a year) data has increased 4.3ºC. In another side, the CO2 multiplication effect has occurred at 06.30-08.00 AM according to surface and vertical profile measuremens, due to stable atmosphere and calm wind. Key words: Surface fixed system, CO2 concentration, Convection